(untitled) (Research, Society and Development, 2022)
Silicon has been associated with beneficial effects on plants such as tolerance to water deficit, salt stress and reduced transpiration. This work aimed to evaluate the effect of silicon application on the development and productivity of corn submitted to different periods of water deficit in the semi-arid region of Piauí. The experimental design used was a randomized block design, in a 4x2 factorial arrangement, formed by the combination of four silicon doses (0, 50, 100 and 200% of the recommended dose) and two water deficit conditions (moderate and severe), with four repetitions. The recommended dose was 1.0 L ha-1 of silicate, according to the manufacturer. The variety used was the super early BRS Gorutuba. Each plot consisted of four 4.0 m rows spaced at 0.80 m from each other, with the central rows being considered as useful area and the outer rows as border. The data were submitted to variance analysis using the F test. To verify the optimal silicon dose, for each stress intensity, polynomial regression analysis was applied (P<0.05).There was a significant interaction effect for the variables aboveground fresh mass, aboveground dry mass, and yield. Doses of 0.84 and 0.55 L ha-1 of silicon were the most indicated for moderate and severe deficit, respectively. Doses above 1L ha-1 reduced the growth and productivity of corn.